Effect of additions on the self-compacting concrete's absorption - Rachid Rabehi; Amieur Mohamed; Rabehi Mohamed; Omrane Mohammed (The Journal of Engineering and Exact Sciences)
Self-compacting concretes (SCC) are unique concretes that have been developed over the past 30 years. They have the distinct property of being very fluid. Even though they have a great deal of potential for growth, they are still classified as "new concretes" today because of their modest use. SCC differs from conventional vibrated concrete (OVC) in that it is extremely flexible and does not involve the use of vibration. They can be cast in places where there is a high reinforcement density because they compact under the weight of their own mass. In order to reduce the amount of cement caused by the increase in paste volume required to allow the concrete to flow, a large volume of mineral addition is required for the formulation of self-compacting concretes. The main goal of this research was to use the capillary absorption test to determine the impact of various cementitious additions (limestone filler (Lf), brick waste powder (Br), and crushed dune sand (Sd)) by partially substituting a specific amount of Portland cement on the SCC. The findings indicate that, with the exception of brick, all self-compacting concretes produce intriguing results in terms of compressive strength and water absorption.